Rancang Bangun Pengaman Rumah dan Kontrol Pada Kunci Pintu dengan Metode Kriptogafi Hill Cipher Berbasis IoT - Nasron, Nasron; Suroso, Suroso; Buana, Chandra (Program Studi Teknik Elektro Universitas Khairun, 2020)
Various kinds of problems are threatening homeowners from the danger of fire to the danger of theft. To reduce the crime rate that occurs in the community, especially the crime of theft and fire hazard, we need an Internet-based home security tool that can be used to access and obtain reports on the condition of the house directly. In this study the design of a unit of home security equipment was carried out using Arduino as a microprocessor to connect software and hardware by combining several sensors to monitor the home security. Sensors used include Passive Infra Red (PIR) to detect moving objects, MQ-2 sensors to detect smoke and solenoid door lock to lock doors that can be controlled and monitored through the android application as an interface used by its users. The research method used is the cryptographic method with the hill cipher algorithm as a safety data command given to the sensor device and door lock. The results of this study in the form of a home security system that is useful for monitoring the state of the house through an android mobile phone when detecting people or smoke that can endanger the situation when the house is empty, and can control the door lock and sensors remotely.